Gonads or body? Differences in gonadal and somatic photoperiodic growth response in two vole species - van Rosmalen, Laura; van Dalum, Mattis Jayme; Hazlerigg, David; Hut, Roelof A. (Journal of Experimental Biology, 2020)
To optimally time reproduction, seasonal mammals use a photoperiodic neuroendocrine system (PNES) that measures photoperiod and subsequently drives reproduction. To adapt to late spring arrival at northern latitudes, a lower photoperiodic sensitivity and therefore a higher critical photoperiod for reproductive onset is necessary in northern species to arrest reproductive development until spring onset. Temperature–photoperiod relationships, and hence food availability–photoperiod relationships, are highly latitude dependent. Therefore, we predict PNES sensitivity characteristics to be latitude dependent. Here, we investigated photoperiodic responses at different times during development in northern (tundra or root vole, Microtus oeconomus ) and southern vole species (common vole, Microtus arvalis ) exposed to constant short (SP) or long photoperiod (LP). Although the tundra vole grows faster under LP, no photoperiodic effect on somatic growth is observed in the common vole. In contrast, gonadal growth is more sensitive to photoperiod in the common vole, suggesting that photoperiodic responses in somatic and gonadal growth can be plastic, and might be regulated through different mechanisms. In both species, thyroid-stimulating hormone β-subunit ( Tshβ ) and iodothyronine deiodinase 2 ( Dio2 ) expression is highly increased under LP, whereas Tshr and Dio3 decrease under LP. High Tshr levels in voles raised under SP may lead to increased sensitivity to increasing photoperiods later in life. The higher photoperiodic-induced Tshr response in tundra voles suggests that the northern vole species might be more sensitive to thyroid-stimulating hormone when raised under SP. In conclusion, species differences in developmental programming of the PNES, which is dependent on photoperiod early in development, may form different breeding strategies as part of latitudinal adaptation.